RECEPTION OF ADOLESCENTS ON MOTIVATION IN PODCAST - Devi Arina Avrita Putri; Diana Amalia (Jurnal Ilmu Komunikasi, 2020)
In the era of technological developments new media emerging that can increase social interaction between people for example is Podcast. One very interesting account is Merry Riana's podcast account. Merry Riana's Podcast account jumped to the first rank in Apple Podcast with motivational genre in just one month. Because the researcher wants to find out how adolescent acceptance of motivation is in the Merry Rianaepisode 11,74 and 84 podcasts. This study aims to find out adolescent acceptance of motivation messages by Merry Riana on her podcast account, the researcher chooses 3 episodes. This study uses the theory of ecoding decoding by Stuart Hall. The results of this study indicate the acceptance of adolescents to Merry Riana's motivation Podcast at the dominant level of hegemony, the content of motivational messages contained in the podcast can be a motivation that has a strong influence on informants because the informant sees from Merry Riana's background that is a motivator and his life background is full of challenges, In addition, the informant who is in a dominant position believes that motivational messages are inspirational and can open ways of thinking while in a negotiating position suggest that motivational messages are good when delivered in according to the selection of appropriate themes or titles. In the opposite position motivational messages cannot influence because infomans prefer motivated by the closest person because there is emotional closeness, another informant said that the motivational message was not easy to understand due to different educational backgrounds.